Reflections on operators' competition in big data of internet of things - Nan LIU; Lu LIU; Di ZHANG; Jinwu WEI; Yunyong ZHANG (Dianxin kexue)
By analyzing the layout of different industry in the big data of IoT,promoting IoT big data is the breakthrough to the innovative business of operators.Different strategies in the aspects of data,platform and application should be carried out in order to build core competitiveness for operators in big data of IoT.